Guide :

# factor the trinomial 5x^2-15x-140

factor completely 5x^2-15x-140 this is a trinomial

## Research, Knowledge and Information :

### How do you factor the trinomial 25x^2-15x+2? | Socratic

Factor: y = 25x^2 - 15x + 2 Ans: (5x - 1)(5x - 2) ... How do you factor the trinomial #25x^2-15x+2#? Algebra Polynomials and Factoring Factorization of Quadratic ...

### 5x^2+15x-140=0 - solution - Get Easy Solution

Simple and best practice solution for 5x^2+15x-140=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so ...

### How do you factor the trinomial 3x^2-15x+16? | Socratic

How do you factor the trinomial #3x^2-15x+16#? Algebra Polynomials and Factoring Factorization of Quadratic Expressions. 1 Answer ? 1 Shwetank Mauria ...

### Factor the Trinomial 5x^2 - 14x - 3 - YouTube

Jun 13, 2012 · How to factor a trinomial with a leading coefficient other than 1. http://www.openalgebra.com/

### How to factor this trinomial 5x^2+3x-14? | eNotes

Get an answer for 'How to factor this trinomial 5x^2+3x-14?' and find homework help for other Math questions at eNotes

### Factoring Trinomials using AC Method - Think Smart

Factoring Trinomials using AC Method ... Factor 12x 2 + 5x - 2 1. ... the middle term in the trinomial. The order of the 2 terms doesn’t

### Which of the binomials below is a factor of this trinomial ...

Which of the binomials below is a factor of this trinomial? - 2106034 ... Which of the binomials below is a factor of this trinomial? 5x^2 + 15x - 50 A. x + 10 B. x ...

### Factoring by Grouping - MathBitsNotebook(A1 - CCSS Math)

There are many different applications of factoring by ... becomes the focus of the process of factoring by grouping for a trinomial. ... Factor: 5x 3 + 15x 2 - 10x - 30.

## Suggested Questions And Answer :

### can you break this problem down for me so I can see how it is solved

x^2 - 15x + 16 = 0 That would factor nicely if it was x^2 - 15x - 16 = 0, but x^2 - 15x + 16 = 0 doesn't factor nicely. Quadratic formula x^2 - 15x + 16 = 0 x = (15 +- sqrt((-15)^2 - 4(1)(16))) / 2(1) x = (15 +- sqrt(225 - 64)) / 2 x = (15 +- sqrt(161))/2 sqrt(161) doesn't factor, so the answer is: x = (15 + sqrt(161))/2, (15 - sqrt(161))/2 . 3x^2 + 3x = 8 3x^2 + 3x - 8 = 0 (3x   )(x   ) = 0 That looks like it might not factor nicely, so. . . quadratic. x = (-3 +- sqrt(3^2 - 4(3)(-8))) / 2(3) x = (-3 +- sqrt(9 + 96)) / 6 x = (-3 +- sqrt(105))/6 Sqrt(105) doesn't facto, so the answer is: x = (-3 + sqrt(105))/6, x = (-3 - sqrt(105))/6 . 7x^2 + x - 6 = 0 (7x   )(x   ) = 0 (7x - 6)(x + 1) = 0 7x - 6 = 0 7x = 6 x = 6/7 x + 1 = 0 x = -1 x = -1, x = 6/7

### Write the polynomial in factored form. x^3 + 7^2 + 15x + 9

If you mean x^3 + 7^2 + 15x + 9 then: x^3 + 49 + 15x + 9 x^3 + 15x + 58 does not have any rational zeros. (can't factor) If you mean x^3 + x^2 + 15x + 9 then: . . .it also appears to not have any rational zeros. If you mean x^3 + 7x^2 + 15x + 9 then: Let's try -1. . . f(x) = x^3 + 7x^2 + 15x + 9 f(-1) = -1 + 7 - 15 + 9 f(-1) = 0 So -1 should work as a root, meaning we should be able to factor out (x+1). Note:  If -1 is a root then x = -1 means x + 1 = 0, which means (x+1) should be a factor in x^3 + 7x^2 + 15x + 9 (x + 1)(???x^2 + ??x + ?) = x^3 + 7x^2 + 15x + 9 x * ???x^2 = x^3, so ??? = 1 1 * ? = 9, so ? = 9 (x + 1)(x^2 + ??x + 9) = x^3 + 7x^2 + 15x + 9 The 15x comes from x * 9 + ??x * 1: 9x + ??x = 15x ??x = 6x ?? = 6 (x + 1)(x^2 + 6x + 9) = x^3 + 7x^2 + 15x + 9 (x + 1)(x + 3)(x + 3) Answer:  (x+1)(x+3)^2

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}

### (8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -8 + 8x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + 4x + -1x2) = 0 Factor a trinomial. 2((-2 + x)(2 + -1x)) = 0 Ignore the factor 2. Subproblem 1 Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2 Subproblem 2 Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2 Solution x = {2, 2}

### findall rational zeros of the polynomial p(x)=x^4-x^3-5x^2+3x+6

p(x) = x4 - x3 - 5x2 + 3x + 6 ⇔p(-1) = 1 + 1 - 5 - 3 + 6 = 0 ⇒x + 1 is a factor p(2) = 16 - 8 - 20 + 6 + 6 = 0 ⇒ x - 2 is a factor ⇒(x4 - x3 - 5x2 + 3x + 6)/(x2 - x - 2) = x2 - 3 ⇒x4 - x3 - 5x2 + 3x + 6 = (x2 - x - 2)(x2 - 3) = 0 ⇒(x - 2)(x + 1)(x2 - 3) = 0 ⇒x = -1, 2, root of 3, - root of 3

### 15xsquared+70x-25

Problem: 15xsquared+70x-25 factoring trinomials by trial and error for my intermediate math class in college 15x^2 + 70x - 25 There are two ways to factor this expression. (15x - 5)(x + 5) 15x^2 + 75x - 5x - 25 15x^2 + 70x - 25 (3x - 1)(5x + 25) 15x^2 + 75x - 5x - 25 15x^2 + 70x - 25

### (13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: x + -3x = -2x -3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Reorder the terms: -3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2 Combine like terms: 5 + -5 = 0 -3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2 -3 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 -3 + -2x + x2 = 0 + -1x2 + x2 -3 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 -3 + -2x + x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-1, 3}

### Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}

### What is the answer to the Factoring Trinomials by Trial and Error problem 3x squared + 11x + 10?

3x^2 + 11x + 10 first ask what multiplies to make 3x^2   (3x    )(x     ) then what multiplies to make 10 (2 and 5) the question is where to put each number (this is where trial and error comes in if you start with (3x + 2)(x + 5) and FOIL you get 3x^2 + 15x + 2x + 10....notice that 15x + 2x = 17x not the 11x that you need so try again, but switch the 2 and 5 (3x + 5)(x + 2) then 3x^2 + 6x + 5x + 10...notice that 6x + 5x = 11x so answer is (3x + 5)(x + 2)

### It can be shown that 2x-1 is a factor of the polynomial function f(x) = 30x^3 + 7x^2 -39x + 14.

Since 2x-1 is a factor of f, x=1/2 is a zero, because 2x-1=0, 2x=1, x=1/2. Synthetic division will help to find other factors: 1/2 | 30...7 -39 14 ........30 15..11 14 ........30 22 -28 | 0 The quotient is 30x^2+22x-28 so f(x)=(x-1/2)(30x^2+22x-28)=(2x-1)(15x^2+11x-14). k=1/2 and q(x)=30x^2+22x-28. We now look at factorising 15x^2+11x-14=(3x-2)(5x+7) so f(x)=(2x-1)(3x-2)(5x+7).